The Impact of Basel III on Trade Finance: The Potential Unintended Consequences of the Leverage Ratio - Marc Auboin; Isabella Blengini (Center for Economic Studies and ifo Institute (CESifo), 2014)
Trade finance, particularly in the form of short-term letters of credit has received favourable capital treatment new Basel III rules. However, concerns have been expressed over the potential negative unintended consequences of the newly created leverage ratio for trade. This paper offers a relatively simple model approach showing the conditions under which the 100% leverage tax on assets such as letters of credit would reduce their natural attractiveness relative to higher-risk ones, which stand in the balance sheet of banks. The decision by the Basel Committee in early 2014 weakening the leverage ratio on trade instruments seems to support the analytical framework developed in this paper.
Keywords: E44; F13; F34; F36; O19; G21; G32; 330; trade financing; cooperation with international financial institutions; prudential supervision and trade